1994
DOI: 10.3109/00016359409096370
|View full text |Cite
|
Sign up to set email alerts
|

Tooth crown size and morphology in Turner syndrome

Abstract: The aims of this investigation were to analyze permanent tooth crown size and morphology and to perform symmetry analysis between corresponding teeth on the right and the left side. The material comprised 32 Turner syndrome patients aged 7-16.7 years. As controls served 33 normal girls 10.2-16.7 years old. The mesiodistal diameter was significantly reduced for every tooth measured except for the maxillary canine. The buccolingual dimension was reduced only for some teeth. Eleven morphologic traits were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
5
25
0
2
Order By: Relevance
“…This latter finding differs from the present results as we now found significant differences in tooth crown height between the 45,X and 45,X/46,XX females, but not between the 45,X/ 46,XX and control females. Taken together, the previous reports and the present work demonstrate a direct effect of sex chromosome genes on the growth of certain tooth groups [25,27,36], tooth roots and crowns [13,15,25] and the different parts of the tooth crown [12,17,19,37].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This latter finding differs from the present results as we now found significant differences in tooth crown height between the 45,X and 45,X/46,XX females, but not between the 45,X/ 46,XX and control females. Taken together, the previous reports and the present work demonstrate a direct effect of sex chromosome genes on the growth of certain tooth groups [25,27,36], tooth roots and crowns [13,15,25] and the different parts of the tooth crown [12,17,19,37].…”
Section: Discussionsupporting
confidence: 66%
“…Varrela et al [11] found that the tooth crowns of 45,X and 45,X/46,XX females (a female with one X cell line and one normal XX line) were almost the same in the mesiodistal direction, while the 45,X/46,XX females had larger crowns in the labiolingual direction. The reduction in tooth crown size in the mesiodistal and labiolingual dimensions in Turner patients has been shown to be primarily caused by a thinner layer of enamel [16,17], although the crown dimensions may also be affected by the changed crown morphology [12,13,18,19]. Measurements performed on dental casts from individuals with various sex chromosome constitutions [3,19] and on the natural teeth of normal females and males [20] have demonstrated sexual dimorphism in average tooth crown sizes, the Y chromosome having been shown to increase both tooth crown enamel and dentin growth, whereas the effect of the X chromosome seems to be restricted to enamel formation [16,17,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 , mezio-distal çaptaki azalmadan daha sıklıkla bahsedilmiştir. 26,46,47,49,50,53 Ayrıca süt dişi kuron boyutlarında da sapma olduğu bildirilmiştir. 18,51,55 Bu hastalarda dişlerin kuron çapının küçülmesi bir çok etkene bağlı olmasına rağmen , mine kalınlığındaki azalma birinci derecede sorumlu tutulmuştur.…”
Section: Dental Bulgularunclassified
“…28,32 Turner sendromunda daimi diş sürmesinde gecikme, küçük dişler, basit kron morfolojileri, ince mine, kı-sa kökler ve idiopatik kök rezorbsiyonları gibi dental anomalilere rastlanmaktadır. 33,34 Rizell ve ark.nın 35 Turner sendromunun karyotiplerinin kron genişliği üzerin-deki etkilerini araştırdığı çalışmada, kron boyutunun X kromozumuyla ilişkili olduğu ve izokromozom karyotipin en düşük kron boyutu gösterdiği tespit edilmiştir.…”
Section: Kraniofasiyal Bulgularunclassified